Clinical Gitelman Syndrome with Periodic Paralysis and Anemia - Muhammad Saiful Rahman; Leonita Anniwati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Gitelman syndrome is a rare, autosomal recessive, renal tubular salt-wasting disorder characterized by hypokalemia and metabolic alkalosis combined with hypomagnesemia and hypocalciuria. A 13-year-old male patient came with acute flaccid paralysis, pain, and weakness in limb muscles. Laboratory results showed hypokalemia, hypocalcemia, hypomagnesemia, and metabolic alkalosis accompanied by anemia and elevated serum transaminases. An electrocardiogram test showed a prolonged QT wave. Physical examination showed blood pressure 118/68 mmHg; heart rate 95x/minute; respiration rate 26 2 x/minute; temperature 37.6â°C, weight 80 kg, height 160 cm, and BMI 31.25 kg/M. Neurological examination weakness in the lower limb, negative pathological reflex. Hematology examination showed Hb 9.8 g/dL, MCV 82.3 fL, MCH 26.8 pg, MCHC 32.5 g/dl, WBC 16.87x10³/Î¼L, platelets 320 x10 / Î¼L, serum iron 47 mg/dL, TIBC 229 mg/dL, ferritin 38.45 ng/mL. Peripheral blood smear showed hypochromic microcytic anemia. Blood gas pH 7.47; pCO2 39 mmHg; pO2 44 mmHg; HCO3- 28.4 mmol/l; Beecf 4.7 mmol/l; SO2 83%; AaDO2 114; thus supporting metabolic alkalosis. Cortisol level was 11.39 ug/dL, ANA test result was positive at 17.2 IU/mL, the complement level was normal, dsDNA antigen was negative. Due to hypokalemia, hypocalcemia, hypomagnesemia, and metabolic alkalosis, this patient was diagnosed with Gitelman syndrome with anemia. The diagnosis should be confirmed by molecular DNA diagnostic studies to identify mutations of the gene encoding the thiazide-sensitive Na-Cl-cotransporter.